Performance of two multiplex flow cytometric assays for antibody detection in Egyptian patients - Alshymaa A. Ahmed; Alia A. El Shahaway; Heba M. Kadry; Nora M. Said (AOSIS, 2023)
Background: Autoantibodies are vital biomarkers for the diagnosis, assessment and prognostic determination of various autoimmune disorders. Objective: This study aimed to evaluate the performance of the two AtheNA Multi-Lyte® systems for the detection of various autoantibodies. Methods: A total of 105 systemic lupus erythematosus patients, 35 patients with other autoimmune diseases (diseased controls), and 30 healthy volunteers (healthy controls) at Zagazig University Hospitals, Zagazig city, Al Sharqia governorate were tested for anti-double-stranded DNA (anti-dsDNA) antibodies using indirect immunofluorescence (IIF) and the AtheNA Multi-Lyte® anti-nuclear antibodies-II system between May 2020 and April 2022. Seventy-five patients with clinically suspected autoimmune vasculitis (AIV) and 25 healthy volunteers were also tested for anti-myeloperoxidase and anti-proteinase 3 antibodies using IIF, the AtheNA Multi-Lyte® AIV system, and enzyme-linked immunosorbent assay (ELISA). Results: The AtheNA anti-dsDNA test (98.5%) was more specific than IIF (96.9%) for diagnosing systemic lupus erythematosus, but both tests had the same sensitivity (38.1%). Combining both methods increased sensitivity to 47.6%, while increasing the cut-off of the AtheNA anti-dsDNA test to 134 international units/mL increased specificity to 100%. The AtheNA Multi-Lyte AIV system exhibited substantial agreement with IIF regarding anti-myeloperoxidase testing (κ = 0.65) and almost perfect agreement with ELISA (κ = 0.85). The AtheNA Multi-Lyte® AIV system exhibited perfect agreement with IIF (κ = 1) and substantial agreement with ELISA for anti-proteinase 3 testing (κ = 0.63). Conclusion: AtheNA Multi-Lyte® systems appear to be reliable for anti-dsDNA, anti-myeloperoxidase, and anti-proteinase 3 screening and may be an optimal choice for monitoring anti-dsDNA levels. What this study adds: It is necessary to evaluate various autoantibodies detection assays to increase both sensitivity and specificity of autoimmune diseases diagnostic approaches. AtheNA Multi-Lyte® systems appear to be reliable for anti-dsDNA, anti-myeloperoxidase, and anti-proteinase 3 screening and may be an optimal choice for monitoring anti-dsDNA levels.